The conversion of biomass into renewable jet fuel. (15th June 2020) - Chen, Yu-Kai; Lin, Cheng-Han; Wang, Wei-Cheng
Abstract: Producing renewable jet fuels from solid waste contributes greatly on circular economy with respect to the energy, environment and economics. The feedstock sources are resolved, the solid wastes are re-used, the pollution from aircrafts are reduced and the air energy is renewed. In this study, the rice husk biomass, which has been a headache agriculture waste in Taiwan, was turned into products similar to traditional jet fuel through fluidized bed fast pyrolysis, hydro-processing and hydro-cracking/isomerization, in which significant increases in normal alkanes, iso-alkanes and cycloalkanes were found. The final product from hydro-cracking/isomerization contained appropriate amount of normal, iso-, and cyclo-alkanes, which made it suitable to be the replacement for jet fuel. Highlights: Renewable jet fuel was produced from local agriculture wastes. Process includes fast pyrolysis, hydro-processing and hydro-isomerization/cracking. Final fuel contains proper amount of normal, iso- and cyclo-alkanes similar to JP5.